General practitioners and preconception weight management in New Zealand. (17th March 2017) - Fieldwick, Diana; Smith, Alesha; Paterson, Helen
Abstract : Background: Childhood obesity is a growing concern internationally and a top priority for the World Health Organization. Preconception overweight, obesity and excess gestational weight gain significantly increase childhood obesity risk. Optimising preconception weight is a key preventative measure toward reducing childhood obesity. In 2014, the New Zealand (NZ) Ministry of Health released guidance for health practitioners on healthy weight gain in pregnancy in an effort to reduce the burden of childhood obesity. Aim: To explore the knowledge and practice of NZ general practitioners (GPs) regarding preconception and gestational weight management. Materials and methods: A nationwide survey was conducted on a randomly selected sample of NZ GPs using a mixed methods approach. Descriptive statistics were used for survey responses and a general inductive approach was applied to the free text data. Results: A total of 200 GPs (42.5%) responded. The majority of GPs were aware of the risks of obesity in pregnancy. Over 50% of GPs reported practice that was not consistent with recommended standards of care. Ministry of Health guidance was known to only 12% of participants. Themes emerging from the free text data included: lack of opportunity for, and awareness of, preconception care; recognition of the importance of this area; and need for further learning. Conclusions: General practitioners in NZ are not providing optimal preconception care. This research highlights the need for a public health message encouraging preconception counselling and better education of GPs on the topic. This should start with promotion of the Ministry of Health guidance.